Making Cognitive Insights on Memory Evident in OBT Projects - Liriano, Fausto (The Bible translator, 2025)
Cognitive memory principles have been integrated into oral Bible translation (OBT) projects in which we employ a collaborative workshop model for translating biblical passages. A structured methodology has been used in two-week workshops, where translators engage in an intensive process of internalization, translation, memorization, and performance of biblical passages. It has proven important to emphasize the role of different types of memory in these specific translation workshops. Memorization and performance have a transformative impact on translators’ comprehension of the text, their collective identity, and hence overall quality assurance, as well on the affirmation of cultural oral traditions within faith communities.